Two-dimensional W2C cathodes for fluoride-ion batteries: Achieving fast ion transport via vacancy induction - Wang, Chuang; You, Lidong; Sun, Tingting; Zhang, Zichun (Electrochemistry communications, 2025)
The two-dimensional W2C sparked widespread interest due to high physicochemical stability and large specific surface area. Fluoride-ion batteries (FIBs) are promising candidates in energy storage applications due to excellent properties such as high energy density. Despite such potential, the role of these materials in FIBs needs elucidation, especially regarding the effect of the fluoride ion transport mechanism on the material surface. In this study, the suitability of W2C as a cathode material for FIB was evaluated for the first time using the vacancy induction method based on first-principles calculations. The results show that the diffusion barrier for fluoride ions on the W2C surface is drastically reduced from 0.26 eV to 0.11 eV, and the ion transport efficiency is more than doubled, while a high theoretical voltage of 4.32 V and stable cycling at a concentration of 0–175 % F− are achieved. This is attributed to the fact that vacancy defects reduce the binding affinity of tungsten to fluoride ions and promote desorption of fluoride ions. This study highlights the importance of vacancy-induced techniques in enhancing 2D materials' ion transport capacity, providing valuable insights for advancing high-performance FIB designs. •Vacancy-engineered W2C reduces F− diffusion barrier by 57 % (0.11 eV) and achieves 4.32 V with stable cycling at 0–175 % F−.•W1.78C0.89 shows thermal stability (300–500 K) via AIMD simulations.•Vacancies diversify F− adsorption sites & weaken binding, enabling rapid desorption.